2013
DOI: 10.1093/icvts/ivt491
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin for reducing postoperative blood loss and transfusion requirements following cardiac surgery in adults

Abstract: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was, in adult patients undergoing cardiac surgery requiring extracorporeal cardiopulmonary bypass (CPB), does administration of desmopressin acetate (DDAVP) reduce postoperative blood loss and transfusion requirements? Altogether 38 papers were found using the reported search, of which 19 represented the best evidence to answer the clinical question. The authors, journal, date and country of publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
0
29
1
Order By: Relevance
“…DDAVP is approved for the treatment of inherited coagulation defects such as Von Willebrand's disorder and can be used off‐label for acquired hemorrhagic conditions such as bleeding in uremic patients. A recent best evidence review concluded that DDAVP may decrease bleeding in patients undergoing CPB who: (a) received aspirin within 7 days of surgery, (b) had CPB times > 140 minutes, and (c) demonstrated platelet dysfunction 21 . We found no significant differences noted between the two groups of this study with respect to DDAVP usage or dose; approximately half of the patients in each group received DDAVP.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…DDAVP is approved for the treatment of inherited coagulation defects such as Von Willebrand's disorder and can be used off‐label for acquired hemorrhagic conditions such as bleeding in uremic patients. A recent best evidence review concluded that DDAVP may decrease bleeding in patients undergoing CPB who: (a) received aspirin within 7 days of surgery, (b) had CPB times > 140 minutes, and (c) demonstrated platelet dysfunction 21 . We found no significant differences noted between the two groups of this study with respect to DDAVP usage or dose; approximately half of the patients in each group received DDAVP.…”
Section: Discussioncontrasting
confidence: 48%
“…18 Intraoperatively platelet dysfunction. 21 We found no significant differences noted between the two groups of this study with respect to DDAVP usage or dose; approximately half of the patients in each group received DDAVP. Recombinant activated factor VII has been used in the setting of acute hemorrhage as well as uncontrolled bleeding postcardiac surgery.…”
Section: Discussionmentioning
confidence: 51%
“…The effects of DDAVP on bleeding in patients having cardiac surgery are summarized in a Cochrane systematic review of 29 RCTs 256 and 2 metaanalyses. 222,257 Summing up the evidence, the prophylactic use of DDAVP did not reduce blood loss (weighted mean difference 241 ml, 95% CI -387.55 to -96.01 ml) or the risk of blood transfusions (OR 0.96, 95% CI 0.87-1.06). Recently published meta-analyses concluded that DDAVP has a small effect on the volume of blood loss and allogeneic blood product transfusions.…”
Section: Prothrombin Complex Concentratementioning
confidence: 99%
“…Pharmacological options to control peri‐operative bleeding consist of topical agents, antifibrinolytic drugs, and drugs that improve primary and/or secondary hemostasis. Among the latter drugs, desmopressin (1‐deamino‐8‐ d ‐arginine vasopressin, DDAVP) has been extensively studied in several types of surgical intervention, but mostly in patients undergoing cardiac surgery with extracorporeal circulation . Desmopressin stimulate increases in plasma concentrations of factor VIII and von Willebrand factor and exerts other, less well‐characterized pro‐hemostatic effects …”
mentioning
confidence: 99%